Strength asymmetries and their impact on landing dynamics during countermovement jump and drop jump tests in professional female basketball players - Acar, N. E.; Umutlu, G.; Gencer, Y. G.; Güven, E.; Tasman, G. A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Injury prevention is a critical concern for female basketball players, particularly in preventing lower limb injuries associated with improper landing mechanics. This study aimed to investigate the relationship between muscle strength (knee, hip, ankle, and trunk) and landing kinematics during Countermovement Jump (CMJ) and Drop Jump (DJ) tasks in female basketball players. Specifically, the objectives were to (1) compare strength discrepancies between dominant and non-dominant limbs, (2) compare landing metrics during CMJ and DJ tasks, and (3) examine the interactions between muscle strength and landing, braking, and sway components to understand the specific role of these muscle groups in optimizing landing mechanics for female basketball players.